Speed vs effort - Goldsmith, W. (coachesinfo.com)
Speed is the most crucial element in the sport. It's fundamental. The swimmer who swims fastest, wins the race. But is it really that simple? This question is answered. One of the crusial points is: Can you learn to relax when trying to go fast?